Facile fix of porous composite titania photocatalytic film by PEO. (2nd June 2016) - Wang, Miao; Guo, Saiya; Wang, Yunlong; Wang, Hao; Yao, Yongjian; Min, Tianxu
Abstract : Porous composite titania photocatalytic films were fixed on steel substrate by plasma electrolytic oxidation. Aluminate solution containing TiO2 nanopowders was used as electrolyte. The microstructure and photocatalytic activities of the films were studied. The investigation results revealed that when the electrolyte contained a few TiO2 powders, the film consisted of A-TiO2, Al2 TiO5 and a few γ-Al2 O3 . With increasing the concentration of TiO2 powders in the electrolyte, γ-Al2 O3 phase disappeared, and the surface content of Ti element increased. The film surface was coarse and porous, which became more and more coarse with more titania powders in the electrolyte. With increasing the concentration of titania powders in the electrolyte, the photocatalytic activity of the film gradually increased. Within 2 h irradiation, the biggest photodegradation ratio of rhodamine B increased to 88% for the film obtained with 8 g L −1 titania powders in the electrolyte.